2004
DOI: 10.1128/jb.186.14.4774-4780.2004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of NopP, a Type III Secreted Effector of Rhizobium sp. Strain NGR234

Abstract: The type three secretion system (TTSS) encoded by pNGR234a, the symbiotic plasmid of Rhizobium sp. strain NGR234, is responsible for the flavonoid-and NodD1-dependent secretion of nodulation outer proteins (Nops). Abolition of secretion of all or specific Nops significantly alters the nodulation ability of NGR234 on many of its hosts. In the closely related strain Rhizobium fredii USDA257, inactivation of the TTSS modifies the host range of the mutant so that it includes the improved Glycine max variety McCall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 39 publications
0
82
0
3
Order By: Relevance
“…Genes responsible for the biosynthesis of the rhizobial T3SS are organized in the tts region, which also contains genes that encode secreted proteins collectively known as nodulation outer proteins (Nops). To date, eight secreted proteins have been identified: NopA, NopB, NopC, NopD, NopL, NopM, NopP and NopX (Ausmees et al, 2004;Bartsev et al, 2003;Deakin et al, 2005;Krishnan, 2002;Lorio et al, 2004;Rodrigues et al, 2007;Saad et al, 2005;Skorpil et al, 2005). Recently, eight proteins have been found to be type III-secreted in B. japonicum; one of them, GunA2, has been identified as an endoglucanase (Süss et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Genes responsible for the biosynthesis of the rhizobial T3SS are organized in the tts region, which also contains genes that encode secreted proteins collectively known as nodulation outer proteins (Nops). To date, eight secreted proteins have been identified: NopA, NopB, NopC, NopD, NopL, NopM, NopP and NopX (Ausmees et al, 2004;Bartsev et al, 2003;Deakin et al, 2005;Krishnan, 2002;Lorio et al, 2004;Rodrigues et al, 2007;Saad et al, 2005;Skorpil et al, 2005). Recently, eight proteins have been found to be type III-secreted in B. japonicum; one of them, GunA2, has been identified as an endoglucanase (Süss et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…strain NGR234 (20) possesses a functional type 3 secretion system (21), which can affect nodulation of host plants either positively or negatively. Up to now, four nodulation outer proteins (Nops) of NGR234 have been identified as type 3 effectors, namely NopL (21-24), NopP (25,26), NopT (27,28), and NopM (28). Their functions remain unclear, however.…”
mentioning
confidence: 99%
“…A large number of plants were associated with nodules because it is inherent characteristics of leguminous plants to form nodules under natural growing conditions Garcia-Fraile et al, 2007). Earlier researchers also did not find host specificity at species or genus level in different rhizobial species and their leguminous host (Ausmees et al, 2004;Singh et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Sinorhizobium species strain NGR 234 formed nodules on more than 100 plant genera (Ausmees et al, 2004). Singh et al (2011) found that S. saheli isolate (PC-6) from Prosopis cineraria was cross infective to Acacia senegal.…”
Section: Resultsmentioning
confidence: 99%